Morphogenesis in pastures with Tanzania grass fertilized with nitrogen doses under a grazing system - Soares, Cecilio Viega [UNESP]; Cecato, Ulysses; Ribeiro, Ossival Lolato; Roma, Claúdio Fabrício Da Cruz; Beloni, Tatiane (Editora da Universidade Estadual de Maringá - EDUEM, 2015)
The morphogenetic and structural characteristics, coupled to forage production of Tanzania grass with nitrogen (N) doses during the seasons of the year, at intermittent grazing, were analyzed. The experimental design consisted of a totally randomized block with split plots and four replications. The plots comprised 0, 150, 300 and 450 kg ha-1 N levels, whereas the sub-plots were the seasons. Urea was applied three times on the pasture and had a positive effect on the rates of leaf elongation and emergence and on the number of live leaves of Tanzania grass in the spring and summer. High nitrogen fertilization associated with shorter grazing intervals triggered a higher percentage of leaf blades in the management of Tanzania grass under rotational stocking at a height of 70 cm on the admittance of animals for grazing and their exit at 30 cm stubble height.

O objetivo do trabalho foi estudar as características morfogenéticas do Panicum maximum Jacq cv. Tanzânia sob o efeito de doses crescentes de nitrogênio (N) nas estações do ano, em pastejo intermitente. O delineamento experimental utilizado foi de blocos completos ao acaso, com parcelas subdivididas no tempo, com quatro repetições. Nas parcelas, encontravam-se as doses de N (0, 150, 300 e 450 kg ha-1 de N) e, nas subparcelas, as estações do ano (outono, inverno, primavera e verão). A adubação nitrogenada exerceu efeito positivo nas taxas de alongamento e aparecimento foliar, e no número de folhas vivas em plantas de capim-Tanzânia nas estações da primavera e verão. Elevadas adubações nitrogenadas associadas a intervalos menores de pastejo promovem maior porcentagem de lâmina foliar, no manejo de pastos de capim-Tanzânia em lotação rotacionada com altura de 70 cm na entrada dos animais para o pastejo e saída com 30 cm de altura do resíduo.
Morfogênese em pastagens de capim-Tanzânia fertilizadas com doses de nitrogênio em pastejo
Keywords: Panicum maximum; grazing; leaf appearance rate; leaf elongation rate; urea.; Panicum maximum; pastagem; taxa aparecimento foliar; taxa de alongamento foliar; ureia.